VALIDATION OF STUDENTS’ WORKSHEETS BASED ON CONTEXTUAL LEARNING APPROACH TO BUILD CRITICAL THINKING SKILLS - Salwa Salsabilla; - Gusnedi (PILLAR OF PHYSICS EDUCATION, 2022)
This research was intended to produce students' worksheets according to contextual learning approach to build critical thinking skills of 10th-grade high school students on linear and projectile motion. The method used in this research is Sugiyono's level 4 research and development method which has been modified and restricted up to the validation stage. The data in this research was obtained based on the results of product validity which were assessed by three experts using validation sheet with six components, namely content feasibility, presentation, linguistics, contextual assessment aspects, critical thinking assessments aspect, and graphics. The obtained data were processed using Aiken's V validation analysis, the results are described through graphs. The results of the V coefficient of the product is 0,86 included in the very high category. So, the students' worksheets according to contextual learning approach to build the critical thinking skills of 10th-grade high school students on linear and projectile motion can be said to be very valid.